Situation Report: Romania, 2 March 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Apollo 12 Astronauts in Bucharest Burtica's Visit to Bonn Ends Deputy Minister of Agriculture Dismissed Romanian Diplomats Again Involved in Espionage Case Draft Law on Labor Discipline Published Meeting of Executives of "Socialist" Writers' Union Ends Rautu's 60th Birthday Economic News